Effect of Sevoflurane on the Deep Neuromuscular Blockade in Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy: A Single Center Prospective Randomized Controlled Study - Shao L; Liu Y; Hao J; Li J; Wang H; Xue FS; Song B; Wan L (Dove Medical Press, 2023)
Liujiazi Shao,1 Yang Liu,2 Junqiang Hao,1 Jiayi Li,1 Hongyu Wang,1 Fu-Shan Xue,1 Bijia Song,1 Lei Wan1 1Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 2Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of ChinaCorrespondence: Bijia Song, Email songbijia@163.comObjective: Our study aimed to demonstrate that the combination of sevoflurane inhalation with continuous intravenous anesthesia can effectively reduce the dosage of muscle relaxants, shorten extubation time under anesthesia while meeting the requirements of laparoscopic deep neuromuscular block (dNMB) in obese patients. Additionally, we sought to assess the potential reduction in postoperative residual muscle relaxants.Methods: Fifty-nine patients were randomly assigned. Anesthesia-related variables, such as anesthetics dosages, muscle relaxant effective time, clinical muscle relaxant time, muscle relaxant in vivo action time, muscle relaxant recovery time, body movement times, and extubation duration were recorded. Surgery-related variables (the Leiden-Surgical Rating Scale (L-SRS), duration of the procedure) were recorded. Pain was measured using the visual analog scale (VAS) score before leaving the PACU. The duration of the PACU stay and patients' satisfaction levels in the PACU were also recorded.Results: Patients who inhaled sevoflurane during the operation required a lower dosage of muscle relaxant to achieve the same deep neuromuscular block (dNMB) effect. The time from stopping the rocuronium pump to T1 recovery of 90% was shorter, and the time for T1 to recover from 25% to 75% was faster among patients who inhaled sevoflurane during the operation. Furthermore, the sevoflurane combined with continuous intravenous anesthesia group exhibited a shorter extubation time for obese patients undergoing laparoscopic bariatric surgery, along with a reduced risk of experiencing hypoxemia and a shorter observation time in the PACU.Conclusion: Inhaling sevoflurane combined with continuous intravenous anesthesia during the operation effectively reduces the dosage of muscle relaxant required to achieve the same deep neuromuscular block (dNMB) effect. Additionally, this approach significantly shortens the extubation time for obese patients undergoing laparoscopic bariatric surgery and reduces the risk of experiencing hypoxemia, along with reducing the observation time in the PACU.Keywords: obese, laparoscopy bariatric surgery, rocuronium, sevoflurane, deep neuromuscular block